PELAKSANAAN CSR PERUSAHAAN TERHADAP MASYARAKAT KECAMATAN RUMBAI TIMUR BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 6 TAHUN 2012 TENTANG TANGGUNG JAWAB SOSIAL PERUSAHAAN - Irfansyah, Irfansyah; Hasnati, Hasnati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies, it is regulated that companies that carry out their business activities in the natural resources sector and/or fields related to natural resources are required to carry out corporate social responsibility. The method used in this study is sociological legal research. The implementation of corporate CSR towards the community of Rumbai Timur District based on Riau Provincial Regulation Number 6 of 2012 concerning Corporate Social Responsibility has not been optimally implemented, especially in the field of preserving customs and culture and empowering local workers. Obstacles in its implementation are the ignorance of the Rumbai Timur District community regarding Riau Provincial Regulation Number 6 of 2012 concerning Corporate Social Responsibility and also the lack of supervision carried out by the Riau Provincial Social Service of companies in Rumbai Timur District. Based on Article 32 of Riau Provincial Regulation Number 6 of 2012 concerning Corporate Social Responsibility, it is regulated that companies that do not carry out CSR can be subject to administrative sanctions in the form of written warnings, restrictions on business activities, freezing of business activities, and revocation of business licenses.Keywords: Company, CSR, Society